Prophylaxis and exclusion: compulsory isolation of Hansen's disease patients in São Paulo - Yara Nogueira Monteiro (História, Ciências, Saúde: Manguinhos, 2003)
This article aims to retrieve the history of Hansen's disease in Brazil, analyzing the medical thinking of the time and the shaping of health policies that permitted the implementation, in São Paulo, of a prophylactic policy of compulsory exclusion for all Hansen's disease patients. It also analyzes how the structuring and implementation of this policy led to a 'São Paulo model' that strongly influenced the rest of the country. It addresses the creation of the state's network of leper colonies, their characteristics and the emergence of a veritable 'parallel state' that endured until 1967, with complete disregard of all the changes taking place in both national and international prophylactic policymaking.